Additional value of biplane transoesophageal imaging in assessment of mitral valve prostheses. Issue 3 (September 1993) - Groundstroem, K; Rittoo, D; Hoffman, P; Bloomfield, P; Sutherland, G R
Abstract : OBJECTIVES–To determine whether biplane transoesophageal imaging offers advantages in the evaluation of mitral prostheses when compared with standard single transverse plane imaging or the precordial approach in suspected prosthetic dysfunction. DESIGN–Prospective mitral valve prosthesis in situ using precordial and biplane transoesophageal ultrasonography. SETTING–Tertiary cardiac referral centre. SUBJECTS–67 consecutive patients with suspected dysfunction of a mitral valve prosthesis (16 had bioprostheses and 51 mechanical prostheses) who underwent precordial, transverse plane, and biplane transoesophageal echocardiography. Correlative invasive confirmation from surgery or angiography, or both, was available in 44 patients. MAIN OUTCOME MEASURES–Number, type, and site of leak according to the three means of scanning. RESULTS–Transverse plane transoesophageal imaging alone identified all 31 medial/lateral paravalvar leaks but only 24/30 of the anterior/posterior leaks. Combining the information from both imaging planes confirmed that biplane scanning identified all paravalvar leaks. Five of the six patients with prosthetic valve endocarditis, all three with valvar thrombus or obstruction, and all three with mitral annulus rupture were diagnosed from transverse plane imaging alone. Longitudinal plane imaging alone enabled diagnosis of the remaining case of prosthetic endocarditis and a further case of subvalvar pannus formation. CONCLUSIONS–Transverse plane transoesophageal imaging was superior to the longitudinal imaging in identifying medial and lateral lesions around the sewing ring of a mitral valve prosthesis. Longitudinal plane imaging was superior in identifying anterior and posterior lesions. Biplane imaging is therefore an important development in the study of mitral prosthesis function.